THE GIVING CONFORMITY ON STIMULATION FOR THE DEVELOPMENT OF CHILDERN - Qurniyawati, Eny (WARTA BHAKTI HUSADA MULIA : Jurnal Kesehatan, 2018)
Not achieving optimal child development result in reduced earnings of as much 20% as adult that have implication for national development of the nation.